Performance Analysis of Solar Panels in Tropical Region: A Study Case in Surakarta Indonesia - Rudi Susanto; Wiji Lestari; Herliyani Hasanah (LPPM Universitas Duta Bangsa Surakarta, 2022)
The performance of solar panels affects the utilization of solar energy for daily life. This study aims to carry out the measurement of the performance of solar panels in Surakarta City is located between 110 ° 45 '15